Pathogenic Microbes Increase Plant Dependence on Arbuscular Mycorrhizal Fungi: A Meta-Analysis - Qin, Mingsen; Miranda, Jean-Pascal; Tang, Yun; Wei, Wangrong; Liu, Yongjun; Feng, Huyuan (Frontiers in Plant Science, 2021)
Numerous studies have confirmed that arbuscular mycorrhizal fungi (AMF) can promote plant nitrogen and phosphorus absorption, and prime systemic plant defense to the plant pathogenic microbes. Despite that, the information on the interaction between AMF and plant pathogenic microbes is limited, especially the influence of plant pathogenic microbes on the effect of AMF promoting plant growth. In this study, 411 independent paired-wise observations from 96 published papers were collected and used to calculate the difference effect of AMF with plant pathogenic microbes (DAPP) in promoting plant growth through meta-analysis. The results shown that AMF had higher effect size on plant growth with pathogenic microbes comparing to without pathogenic microbes, with particularly significant effects in root fresh biomass, and shoot and total dry biomass. The results of the selection models revealed that the most important factor determining the DAPP on plant dry biomass was the harm level of plant pathogenic microbes on the plant dry biomass, which was negatively correlated. Furthermore, the change of AMF root length colonization (RLC) was the sub-important factor, which was positively correlated with the DAPP. Plant life style was also significant in the selection model, and AMF had lower effect with pathogenic microbes for the woody plant shoot dry biomass. Taken together, these results have implications for understanding the potation and application of AMF in agroecosystem.